PENGARUH KUALITAS WEBSITE TERHADAP KEPUASAN PENGGUNA WEBSITE PT. KAI (PERSERO) DENGAN MENGGUNAKAN METODE WEBQUAL 4.0 - Pradana, Mahir; Riyanto, Yusuf (JURNAL KEBANGSAAN, 2017)
Accompanied Technology developments The development of Information Technology-based systems. The development of the information system will be successful if it is supported by some of the supporting factors That can be provide success Alone Against Information Systems The reflected through User Satisfaction Information Systems. USE and Information Systems Technology Advancement NOT Just take effect ON A Management Company but also bring a significant influence hearts Against The different ASPECT Business. One of the interesting phenomena of the development of Information and Communication Technology is the internet as a new medium that can not be separated from the life of todays modern society. New media like the Internet is a medium that can shift traditional media such as television, radio, because new media is interactive so the demand by many people. Internet as a medium of communication that people show interest because of several advantages such as easy, quick and precise. Based on hypothesis testing simultaneously be concluded Ha accepted because the F count larger than F table (28 183> 3:09), which means Usability Quality, Information Quality and Service Interaction Quality simultaneously influence customer satisfaction. As for testing the hypothesis Partial be concluded. Ha accepted, due to the variable Quality Usability own value t is greater than t table (2,724> 2,722), which means Usability Quality proven effect on user satisfaction, and the Information Quality variable t is not greater than t table (-821 2.722),which means the Service Interaction Quality proven effect on user satisfaction Keywords: E-Commerce, User Satisfaction, Consumer Behavior